An international Delphi consensus on patient preparation for metabolic and bariatric surgery - Clyde, Danielle R; Adib, Reza; Baig, Sarfaraz; Bhasker, Aparna G; Byrne, James; Cameron, David; Catalain, Copaescu; Clare, Ken; de Beaux, Andrew; Drummond, Gillian; Fawal, Hayssam; Fried, Martin; et al. (Clinical obesity, 2025)
Global obesity rates have risen dramatically, now exceeding deaths from starvation. Metabolic and bariatric surgery (MBS), initially for severe obesity (BMI ≥35 kg/m2), is performed globally over 500 000 times annually, offering significant metabolic benefits beyond weight loss. However, varying eligibility criteria globally impact patient care and healthcare resources. Updated in 2022, ASMBS and IFSO guidelines aim to standardise MBS indications, reflecting current understanding and emphasising comprehensive preoperative assessments. Yet, clinical variability persists, necessitating consensus-based recommendations. This modified Delphi study engaged 45 global experts to establish consensus on perioperative management in MBS. Experts selected from bariatric societies possessed expertise in MBS and participated in a two-round Delphi protocol. Consensus was achieved on 90 of 169 statements (53.3%), encompassing multidisciplinary team composition, patient selection criteria, preoperative testing, and referral pathways. The agreement highlighted the critical role of comprehensive preoperative assessments and the integration of healthcare professionals in MBS. These findings offer essential insights to standardise perioperative practices and advocate for evidence-based guidelines in MBS globally. The study underscores the need for unified protocols to optimise outcomes and guide future research in MBS.
Keywords: mužské pohlaví; ženské pohlaví; Bariatric Surgery; delfská metoda; Humans; Delphi Technique; Patient Selection; Consensus; Female; Preoperative Care; Male; Obesity, Morbid; předoperační péče; bariatrická chirurgie; lidé; konsensus; výběr pacientů; morbidní obezita